Primitive Myxoid Mesenchymal Tumor of Infancy - Zhang Yu; Guo Wanxu; Zhangyun Feng; Chi Di; Li Yanqing; Liu Junjiao (Elsevier, 2020)
Primary myxoid stromal tumor in infancy is a rare subtype of soft tissue sarcoma, with the feature of infiltration of surrounding tissue, rare metastasis and poor response to chemotherapy. As a result, surgery operation is the most effective among therapies. According to current documents, sarcoma locate in trunk, head, neck and limbs. Here is a case report of PMMTI locating in pharynx and larynx.